2017
DOI: 10.1016/j.jclepro.2017.09.081
|View full text |Cite
|
Sign up to set email alerts
|

Using human-powered products for sustainability and health: Benefits, challenges, and opportunities

Abstract: This paper presents a novel research work on the potential benefits of using, a unique and sustainable energy source-the human-power. The paper discusses the benefits and the practicality of using human-power as a domestic energy source to power electrical and electronic devices and explores the benefit of its use in a more diverse perspective for possible change in behaviour and energy savings for improved sustainability in the society. The economic and sustainability gains of using Human-Powered Products (HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…His study concluded that the financial gain of using human power as an alternative power source was inadequate and further emphasized that the potentiality of such intervention would be more lucrative when used as means to increase PA and reduce sedentary behavior in the home environment. 24 Some studies have shown that even little time spent in light to moderate PA may increase health benefits. 22,[25][26][27] However, there are limitations in the existing literature whereby very few studies have examined the role of parents in modeling habitual PAs or discouraging these screen-related behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…His study concluded that the financial gain of using human power as an alternative power source was inadequate and further emphasized that the potentiality of such intervention would be more lucrative when used as means to increase PA and reduce sedentary behavior in the home environment. 24 Some studies have shown that even little time spent in light to moderate PA may increase health benefits. 22,[25][26][27] However, there are limitations in the existing literature whereby very few studies have examined the role of parents in modeling habitual PAs or discouraging these screen-related behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…By studying these attitudes and determining what impacts them, scholars and policymakers will be better equipped to develop effective strategies for promoting sustainable solutions. Although the necessary technology is yet to be perfected, the implementation of HKE generation systems can become a practical demonstration of renewable energy generation for the general public [46]. In addition to our research, previous studies indicated that wearable and stationary HKE technologies tend to stimulate discussion about sustainability while making observers more enthusiastic about renewable energy use [3,47].…”
Section: Discussionmentioning
confidence: 61%
“…However, social sustainability is primarily measured by employee-related indicators such as working conditions, health, safety, training, and education [120], and applications measuring social sustainability performance in the context of various products and industrial manufacturing lack consistency [121]. For example, Kim selected the easily measurable indicator of toxic substances to represent worker health status in measuring the social sustainability of coffee machines [104], and Shin selected sedentary behavior and physical activity to analyze human-powered products [105]. Simultaneously, uncertainty of what data to utilize for social sustainability assessment and data quality [122] adds to the complexity of sustainable product design, evaluation, and decision-making.…”
Section: Analysis Of Methods Clustering and Research Trendsmentioning
confidence: 99%